-4(-2x+3)=12

Simple and best practice solution for -4(-2x+3)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-2x+3)=12 equation:


Simplifying
-4(-2x + 3) = 12

Reorder the terms:
-4(3 + -2x) = 12
(3 * -4 + -2x * -4) = 12
(-12 + 8x) = 12

Solving
-12 + 8x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 8x = 12 + 12

Combine like terms: -12 + 12 = 0
0 + 8x = 12 + 12
8x = 12 + 12

Combine like terms: 12 + 12 = 24
8x = 24

Divide each side by '8'.
x = 3

Simplifying
x = 3

See similar equations:

| 4x^2-12x=16 | | 9y-2y=14 | | 2a=2 | | 1.6x=8 | | X^3+24x^2+144x=0 | | c^2-24c+82=0 | | 2x^3y^3-24x^2y^4+72xy^5=0 | | 3x+2=2x^2 | | x-7.6=6.6 | | y+38=13 | | x(x-6)+1=x-11 | | (5x-2)(2x+3)=10 | | X^4+2x^3-x-2=0 | | 3=6x+y | | X^3+18x^2+45=0 | | 4x(x-3)+5=0 | | 24x^2+100x-36=0 | | 4ln(7x)=24 | | 35x^2-55x-30=0 | | 30x^2-8x-8=0 | | 6x^2=x+1 | | 5x^2+30x-135=0 | | 3ln(7x)=18 | | x^2+3x+30=0 | | 3x^2+33x+90=0 | | 12(t-3)+3t=5(3t+3)-8 | | X^2+16y^2+6x-64y+57=0 | | 4v^2+12v-72=0 | | 3x^2+33x+30=0 | | 2y+4=90 | | 6x^2-72x+216=0 | | 10w^3=160w |

Equations solver categories